Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

Let $L \{ f(t)\}=F(s)$, show that for all $k \in \mathbb{R}$, $k \neq 0$

$$L \{ \frac{1}{k}f(\frac{t}{k}) \}= F(ks)$$

if, $u=\frac{t}{k}$

$L \{ \frac{1}{k}f(\frac{t}{k}) \}= \int_0^{\infty} \exp^{-(ks)u}f(u)du \stackrel{?}{=} F(ks)$


share|cite|improve this question

$$L \{ f(t)\}=F(s)=\int_0^{\infty} e^{-st}f(t)dt $$

$$L \{ \frac{1}{k}f(\frac{t}{k}) \}= \int_0^{\infty} e^{-st}\frac{1}{k}f(\frac{t}{k})dt$$



$dt=k dx$

$$L \{ \frac{1}{k}f(\frac{t}{k}) \}= \int_0^{\infty} e^{-skx}\frac{1}{k}f(x)k dx=\int_0^{\infty} e^{-skx}f(x) dx=F(ks)$$

share|cite|improve this answer
Thanks! and the another one? – P. M. O. Oct 17 '12 at 19:32
@P.M.O. Others are very different stories. What is your aim in this question? I believe that your title proof was completed – Mathlover Oct 17 '12 at 19:38

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.